Pre-treatment of industrial olive oil mill effluent using low dosage health-friendly cationic polyelectrolytes. Issue 6 (December 2017) - Lourenço, Anita; Arnold, Julien; Gamelas, José A.F.; Cayre, Olivier J.; Rasteiro, Maria G.
Graphical abstract: Highlights: Poly(AAm-MAPTAC) and Poly(AAm-MAPTAC-SMA) polyelectrolytes were synthesized and characterized. Their flocculation performance was evaluated in an industrial oily effluent from an olive oil mill. Hydrophobic modification of the polymers improved the treatment efficiency. Turbidity removal of 90%, COD removal of 47% and total solids removal of 34% were achieved. Abstract: Olive oil production involves a significant annual release of industrial olive oil mill effluent to the environment. These discharges bring serious environmental problems since they are extremely hazardous for the aquatic environment due to their organic matter and high turbidity levels. The present study comprises the development of new, hydrophobically modified, cationic flocculants directed to oily effluents application. A health-friendly formulation was used in their synthesis process performed by inverse-emulsion. In particular, Poly(AAm-MAPTAC) was synthesized in two different polymer compositions and, as well, with the presence of a hydrophobic monomer (Poly(AAm-MAPTAC-SMA)) at several compositions up to 8 wt%. The obtained polyelectrolytes were characterized in terms of final composition, hydrodynamic diameter, zeta potential and molecular weight. Their flocculation performance was evaluated in an industrial oily effluent from an olive oil mill. Results revealed that the hydrophobic modification improves noticeably the flocculation performance of cationic polyelectrolytes in the treatment of olive oil mill effluents. In the best conditions, it was possible to achieve 90% turbidity reduction, 47% COD removal and 34% total solids removal with only 53 mg/L of flocculant. Moreover, 79% of turbidity was reduced after addition of 13 mg/L.